2017
DOI: 10.1007/s11999-017-5413-7
|View full text |Cite
|
Sign up to set email alerts
|

Does Humeral Component Lateralization in Reverse Shoulder Arthroplasty Affect Rotator Cuff Torque? Evaluation in a Cadaver Model

Abstract: The results of this preliminary in vitro cadaveric study suggest that the lateral offset of the RTSA humeral component plays an important role in the torque generated by the anterior and posterior rotator cuff. However, further studies are needed before clinical application of these results. Increasing humeral offset may have adverse effects, such as the increased risk of implant modularity, increasing tension of the cuff and soft tissues, increased costs often associated with design modifications, and other p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
26
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 29 publications
1
26
0
2
Order By: Relevance
“…Previous studies related to ROM of rTSA generally characterize ranges of motions that are contained within a subset of single paths (i.e., abduction, flexion, axial rotation, etc.) . However, conclusions pertaining to implant performance drawn from a subset of investigated motions may be misleading, as it has been shown that differing implant designs maximize different motions .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies related to ROM of rTSA generally characterize ranges of motions that are contained within a subset of single paths (i.e., abduction, flexion, axial rotation, etc.) . However, conclusions pertaining to implant performance drawn from a subset of investigated motions may be misleading, as it has been shown that differing implant designs maximize different motions .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies related to ROM of rTSA generally characterize ranges of motions that are contained within a subset of single paths (i.e., abduction, flexion, axial rotation, etc.). [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]33,34,36,37 However, conclusions pertaining to implant performance drawn from a subset of investigated motions may be misleading, as it has been shown that differing implant designs maximize different motions. 13,36 GC-ROM, which condenses the analysis of a broader ROM, provides a single, generalized performance metric.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of implant lateralization on SSc function and clinical outcomes following SSc repair also remains controversial . Lateralization of the center of rotation in RSA is shown to reduce intra‐articular impingement and scapular notching and increase range of motion (ROM), but it can also reduce the deltoid lever arm, which results in increased glenohumeral shear forces and bending moments on the glenosphere fixation, which is a risk for glenoid loosening.…”
mentioning
confidence: 99%